Análise de minigeração solar fotovoltaica na Universidade Federal de Santa Maria - Pilz, Caroline Obregon (2019)
The following work presents an analysis on the impact and the financial performance of the Solar Photovoltaic Minigeration at the Federal University of Santa Maria, customer of group A4, considering the tariff and regulatory conditions. Related source of energy energy, observation-on the new power sources of electrical energy, beyond levels of generate their own electricity. By the way, consider the charge curves of the consumer unit, the local natural resources, and the system configuration. This database, coupled with the software Hybrid Optimization Model for Renewable Electric Energies (HOMER), made possible an approximation of the current and a second case in a horizon of twenty years. Reduce energy billing and sustainable development, case-study studies for a source of results. Thus, it will be presented a viability of the implementation of the photovoltaic companies in a public educational institution.